Aplicación de la plataforma digital british council como herramienta facilitadora para la comprensión lectora. - Paute Cuero, Angie Stefany; Aguilar Aguilar, Tania Elizabeth (Machala : Universidad Técnica de Machala, 2021)
In this research work, the British Council digital platform is implemented as a tool to facilitate reading comprehension in the English language, due to it allows students to practice in an innovative way a number of exercises, reinforcing and improving their skill. The participant observation showed that most students have little knowledge of the subject, and present difficulties in reading comprehension, resulting in an unfavorable performance. Therefore, the general objective proposed was: To improve the reading comprehension of students in the 9th year of general basic education through the digital platform “British Council” in the year 2021. The paradigm of this research work is mixed. In order to collect the necessary information, the methods used were; participant observation, teacher interview and a initial diagnostic test and a final summative test were implemented in the students of the 9th year of general basic education “Maria Piedad Castillo de Leví” in order to know their development before and after having applied the digital platform and to know if they managed to improve their reading comprehension. It can be concluded that the application of the British Council digital platform in conjunction with the development of reading comprehension strategies generate a positive change in student’s performance, after analyzing the results of the final test it was determined that students managed to improve their reading comprehension and that the implementation of the digital platform acted favorably,
En el presente trabajo de investigación se implementa la plataforma digital British Council como herramienta facilitadora de la comprensión lectora en el idioma inglés debido a que permite al estudiante practicar de manera innovadora un sin número de ejercicios, reforzando y mejorando esta habilidad. La observación participante demostró que los estudiantes poseen conocimiento sobre la materia, pero presentan dificultades en la comprensión lectora resultando en un desempeño un tanto desfavorable. Por lo tanto, se planteó como objetivo general: Mejorar la comprensión lectora de los estudiantes de 9no año de Educación General Básica por medio de la plataforma digital «British Council» en el año 2021. El paradigma de este trabajo de investigación es de carácter mixto, para recolectar la información necesaria se implementaron los métodos de observación participante, entrevista docente, prueba de diagnóstico inicial y una prueba sumativa final en los estudiantes de 9no año de Educación General Básica «María Piedad Castillo de Leví» con el fin de conocer su desarrollo antes y después de haber aplicado la plataforma digital y conocer si lograron mejorar su comprensión lectora. Se puede concluir que la aplicación de la plataforma digital British Council en conjunto con la elaboración de estrategias de comprensión lectora generan un cambio positivo en el desempeño de los estudiantes, luego de analizar los resultados de la prueba final se determinó que los estudiantes lograron mejorar su comprensión lectora y que la implementación de la plataforma digital actuó de manera favorable.
Keywords: BRITISH COUNSIL; PLATAFORMA; COMPRENSION LECTORA; APRENDIZAJE